Determinación de Igg – Igm en el diagnóstico para Toxoplasma Gondii en mujeres embarazadas que son atendidas en clínica Santa Cecila, Machala 2013. - Lam Vivanco, Adriana Mercedes (2015)
Toxoplasmosis is caused by an intracellular protozoan known as Toxoplasma gondii , is considered of great importance in Machala , ignorance of the magnitude of toxoplasmosis in pregnant women in the first tri¬mester of pregnancy , is the main cause of mortality or severe box clinicians to the new living and that is usually asymptomatic , performing a serological screening IgG -IgM antibodies in pregnant women is the only way to detect those , this study will emphasize to diagnose this parasite in the first quarter pregnancy , to prevent disease to the fetus or term born alive, although infection can occur in any trimester of pregnancy, it is important to detect in the first trimester of pregnancy by preventing central nervous system disorders ( internal hydrocephalus , seizures) and retinochoroiditis . Studies determined 18proteínas , actin , catalase , GAPDH ( glyceraldehyde-3- phosphate dehydrogenase ), and three proteins hipotéticastenía Toxoplasma extensive reactivity with positive serum , indicating their potential as diagnostic markers of toxoplasmosis, primordial pattern for determination of toxoplasma gondii , the clinical method was used for this study was by electroquimiolumisencia high sensitivity for the diagnosis of IgG -IgM antibodies , the results of the pre¬valence of IgG antibodies against T. gondii in pregnant women attending the Clinic Santa Cecilia was 16 % IgG anti - IgM seropositive for T. gondii in relation to pregnant women with positive serology for T. gondii decreased linearly with the age of the patient, with the group of 20 - 25years the most affected 40 (12 %) for IgG and IgM positive 25 ( 10% ) taking as reference the prevalence of Toxoplasma gondii.